Motor competence and health related physical fitness in youth: A systematic review. Issue 2 (February 2016) - Cattuzzo, Maria Teresa; dos Santos Henrique, Rafael; Ré, Alessandro Hervaldo Nicolai; de Oliveira, Ilana Santos; Melo, Bruno Machado; de Sousa Moura, Mariana; de Araújo, Rodrigo Cappato; Stodden, David
Abstract: Objectives : This study aimed to review the scientific evidence on associations between motor competence (MC) and components of health related physical fitness (HRPF), in children and adolescents. Design : Systematic review. Methods : Systematic search of Academic Search Premier, ERIC, PubMed, PsycInfo, Scopus, SportDiscus, and Web of Science databases was undertaken between October 2012 and December 2013. Studies examining associations between MC and HRPF components (body weight status, cardiorespiratory fitness, musculoskeletal fitness and flexibility) in healthy children and adolescents, published between 1990 and 2013, were included. Risk of bias within studies was assessed using CONSORT and STROBE guidelines. The origin, design, sample, measure of MC, measure of the HRPF, main results and statistics of the studies were analyzed and a narrative synthesis was conducted. Results : Forty-four studies matched all criteria; 16 were classified as low risk of bias and 28 as medium risk. There is strong scientific evidence supporting an inverse association between MC and body weight status (27 out of 33 studies) and a positive association between MC and cardiorespiratory fitness (12 out of 12 studies) and musculoskeletal fitness (7 out of 11 studies). The relationship between MC and flexibility was uncertain. Conclusions : Considering the noted associations between various assessments of MC and with multiple aspects of HRPF, the development of MC in childhood may both directly and indirectly augment HRPF and may serve to enhance the development of long-term health outcomes in children and adolescents.